2022
DOI: 10.3389/fsufs.2022.847931
|View full text |Cite
|
Sign up to set email alerts
|

Milk, Meat, and Fish From the Petri Dish—Which Attributes Would Make Cultured Proteins (Un)attractive and for Whom? Results From a Nordic Survey

Abstract: Cultured meat, fish, or dairy produced in vitro are discussed as one of the most substantial disruptions the food sector might encounter in the coming decades. These cultured proteins are proposed as a potential solution to the detrimental effects industrial food farming and fishing have on the environment and animal welfare as they would allow people to continue consuming meat, fish, or dairy products while at the same time substantially reducing the burden for the planet. For most people, however, this techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
2
1
0
1
Order By: Relevance
“…The Western European region statistics indicated that consumers in region had a high expected economic and ethical benefit. The positive perceptions about the ethical and economic benefits found in Western Europe studies can be corroborated with findings reported by Klockner et al [ 61 ]. Klockner et al [ 61 ] focused on Western Europe countries (Denmark, Finland and Norway) and found that consumers were most convinced of the possible ethical and economic benefits associated with cultured meat as opposed to other health and safety benefits.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The Western European region statistics indicated that consumers in region had a high expected economic and ethical benefit. The positive perceptions about the ethical and economic benefits found in Western Europe studies can be corroborated with findings reported by Klockner et al [ 61 ]. Klockner et al [ 61 ] focused on Western Europe countries (Denmark, Finland and Norway) and found that consumers were most convinced of the possible ethical and economic benefits associated with cultured meat as opposed to other health and safety benefits.…”
Section: Discussionsupporting
confidence: 87%
“…The positive perceptions about the ethical and economic benefits found in Western Europe studies can be corroborated with findings reported by Klockner et al [ 61 ]. Klockner et al [ 61 ] focused on Western Europe countries (Denmark, Finland and Norway) and found that consumers were most convinced of the possible ethical and economic benefits associated with cultured meat as opposed to other health and safety benefits. The current study's results indicate that the optimism of the ethical and economic benefits of cultured meat is higher than the optimism of the quality, health and safety benefits in Europe and the UK.…”
Section: Discussionsupporting
confidence: 87%
“…However, they have many challenges, including a need for non-food carbon substrates and a possibility for existing mycotoxins [111]. The main target that attracts several scientists all over the world is how to find "plant protein-based meat and dairy analogues" especially under climate change [115][116][117], and single-cell proteins derived from mushrooms as reported by Stephan et al [118] in Table 3. Mushrooms contain many bioactive compounds (e.g., phenolics, polysaccharides, polyketides, steroids, triterpenoids, etc.…”
Section: Unconventional Foods Of Plants and Mushroomsmentioning
confidence: 99%
“…J. Bryant & Barnett, 2019;C. Bryant & Sanctorum, 2021;Circus & Robison, 2018;Egolf et al, 2019;Franceković et al, 2021;Garcez de Oliveira Padilha et al, 2021;Gorgitano et al, 2017;Klöckner et al, 2022;Laestadius & Caldwell, 2015;Lensvelt & Steenbekkers, 2014;Lupton & Turner, 2018a, 2018bOnwezen et al, 2019;Rosenfeld & Tomiyama, 2022;Ruby et al, 2015;Ruzgys & Pickering, 2020;Shaw & Mac Con Iomaire, 2019)Siegrist et al, 2018;Siegrist & Sütterlin, 2017;Slade, 2018;…”
unclassified